Karakteristik Penderita Stroke Iskemik dengan Infark yang Rawat Inap di RSUP Haji Adam Malik Medan Tahun 2012 - Iza Fauziah Simargolang; Jemadi .; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Stroke is a circulatory disorders in the brain that cause physical disability greatest of all degenerative diseases. Stroke is divided into two by pathological is ischemic stroke and haemoragic.To know the characteristics of stroke ischemic patients with infark conducted a Research with case series design in RSUP. Haji Adam Malik Medan. Population and sampel was 117 people in 2012 were recorded in hospital medical records. Univariate data were analyzed descriptively while bivariate data were analyzed using Chi-square test, Mann-whitney and Kruskal wallis. Based on the sociodemographic in highest proportion is age group 45-65 years 65,8%, males 57,3%,Moeslem 60,7%, married 97,4%, Senior high school 44,4%, Housewife 38,5%, dan outside the city of Medan 66,7%. Proportion based on the highest treatment status, weak arm and left leg 38,5%, hypertension 38,5%, basal ganglia 39,3%, hemiparesis sinistra 48,7%, not source 94,9%, Askes 52,9%, the average length ofstay 6,57 or 7 days, outpatient expense control 55,6%. There was a significant difference between infark location with location of the paralysis (p=0,000), and the average treatmenttime with condition while returning (p=0,000).Patient who have a history of hypertension to perform the routine control and Health lifestyle. For the medical records department of RSUP. Haji Adam Malik Medan to complete patient data recording such as ethnic.